A review of biomechanics of the shoulder and biomechanical concepts of rotator cuff repair - Yamamoto, Nobuyuki (Asia Pac J Sports Med Arthrosc Rehabil Technol, 2015)
In this article, we describe the basic knowledge about shoulder biomechanics, which is thought to be useful for surgeons. Some clinical reports have described that the excellent outcome after cuff repair without acromioplasty and a limited acromioplasty might be enough for subacromial decompression. It was biomechanically demonstrated that a 10-mm medial shift of the tendon repair site has a minimum effect on biomechanics. Many biomechanical studies reported that the transosseous equivalent repair was superior to other techniques, although the tendon may lose its inherent elasticity. We herein introduce our recent experiment data and latest information on biomechanics.